2008
DOI: 10.1007/s11434-008-0467-2
|View full text |Cite
|
Sign up to set email alerts
|

Southern rice black-streaked dwarf virus: A new proposed Fijivirus species in the family Reoviridae

Abstract: For the past several years, a novel dwarf disease has been observed on rice (Oryza sativa) in some regions of Guangdong Province and Hainan Province, southern China. Infected plants showed stunting, dark leaf and small enations on stem and leaf back. Typical Fijivirus viroplasma containing crystalline arrayed spherical virons approximately 70-75 nm in diameter and tubular structures were detected in ultrathin sections by an electron microscope in parenchyma phloem cells of the infected plants. The virus was tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
264
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(270 citation statements)
references
References 22 publications
5
264
0
1
Order By: Relevance
“…The nucleotide sequences of segment 9 of SRBSDV and RBSDV were downloaded for the GenBank database, and there was high homology of genome sequence between SRBSDV with RSBDV (74.2~74.9% identity of segment 9) [2]. Sequence multi-alignment was analyzed by software suite of DNAMAN (Lynnon Biosoft Inc, USA).…”
Section: Primers Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The nucleotide sequences of segment 9 of SRBSDV and RBSDV were downloaded for the GenBank database, and there was high homology of genome sequence between SRBSDV with RSBDV (74.2~74.9% identity of segment 9) [2]. Sequence multi-alignment was analyzed by software suite of DNAMAN (Lynnon Biosoft Inc, USA).…”
Section: Primers Designmentioning
confidence: 99%
“…Southern rice black-streaked dwarf virus (SRBSDV), a latest member of the genus Fijivirus within the family Reoviridae, was simultaneously isolated and identified from the rice in southern of China in 2008 [1,2]. In the following three years (2009)(2010), SRBSDV caused the most important rice disease in South of China, there were over ten millions hectare of rice infected, and resulted in massive devastation of rice yield [3].…”
Section: Introductionmentioning
confidence: 99%
“…The causal agent of the rice dwarf disease in the north of Vietnam has also been identified as SRBSDV (Cuong et al, 2009;Hoang et al, 2011). Further investigation suggested that the outbreak of SRBSDV in Vietnam was associated with rising populations of the white-backed plant hopper (Sogatella furcifera), which is the major vector of SRBSDV (Cuong et al, 2009;Zhou et al, 2008). As planthoppers are constantly displaced by wind currents, the spread of the virus diseases they carry will be inevitable.…”
mentioning
confidence: 99%
“…Characteristic symptoms include dark-green and wrinkled leaves, incomplete tassel, tumorlike protrusions ending in small enations, tiller formation on the upper parts, up-growing rootlets, and in particular the presence of white to black waxy galls along the major veins of the leaves and culms (Wang et al, 2012;Zhou et al, 2008;Zhou et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation